Yoga Ice Breaking Sebagai Sarana untuk Meningkatkan Fokus Mahasiswa dalam Belajar Bahasa Inggris - Md. Yudyantara Risadi; Ni Luh Putu Uttari Premananda (Jurnal Yoga dan Kesehatan, 2022)
It is undeniably correct that in the process of learning, there will be a stituaiton where the students feel bored with the material. This situation requires treatments which make the boredom disappear and students improve their focus, one of them is yoga icebreaking. The purposes of this study were to find out what kinds of yoga icebreaking and its benefits. Library research was conducted in this study. The sources of the obtained data coming from articles, publications journal and news using technique of documentation. The technique of analysis used contents analysis of literature or articles becoming the source of research data. The results showed that yoga icebreaking has different moves and it does not take long in the class, such as nostril breathing yoga and Lotus pose. The benefits of this yoga icebreaking are to improve students’ focus and to grow students’ character values.